Complex abdominal gunshot wound, with lower cava and terminal aorta wounds - Aliano, Franklin A; Belloso (h), Rogelio; Soto, José Alberto (Cirugía del Uruguay, 1975)
A case is reported of a complex abdominal bullet wound, with multivisceral lesions and transfixion wounds of inferior vena cava and terminal aorta. It was successfully managed by ligation of the wounded venous elements and by repairing the two aortic orífices by suture. Attention is called to the enormous immediate vital risk involved when the large vessels are affected; to the way for blood volume replacement which should be chosen according to the topography of the wound, nnd to the celerity with which surgical approach must be carried no.